Community Assistance in Efforts to Prevent Mosquito Development by Maintaining Cleanliness and Biopore Creation - Tarisa Alya Ridha; Putri, Inge Wiliandani Setya; Wardoyo, Arik Aguk; Shinta Ayu Suryana; Hadian, Muhammad Nurheza (Edujavare Publishing, 2024)
Public health problems, especially those related to mosquito-borne diseases such as dengue fever and malaria, are often caused by poor environmental conditions. Due to irregular waste disposal, stagnant water becomes a breeding ground for mosquitoes, so the solution is the bio-pore method. This community service aims to eradicate the problem of mosquito breeding by increasing collective awareness and community involvement through the socialization of biopore creation. The community service method uses the Participatory Action Research (PAR) approach. The community service activity was carried out at the student dormitory on Jalan Jawa VI No. 35A, Sumbersari Village, Jember, which students attended. The results of the community service activity showed an increase in participants' understanding and awareness of the importance of biopores in preventing mosquito breeding. Evaluation through questionnaires before and after the socialization showed a significant increase in participants' knowledge and awareness regarding the function and benefits of biopores. The active participation of the community in maintaining environmental cleanliness can create a healthier environment and reduce the risk of diseases transmitted by mosquitoes.